Guiding Principles for Successful Reforms of Urban Water Supply and Sanitation Sectors - Locussol, Alain R. (World Bank, Washington, DC, 2012)
The note proposes a methodology for assessing the accountability framework of an urban water supply and sanitation (WSS) sector that it defines as the set of actors, mandates, contractual arrangements between actors, and instruments used by actors to implement their mandates. The accountability framework focuses on the five key functions of the urban WSS sector that are policy formulation, asset management and infrastructure development, service provision, financing, and regulation of the service. The note recommends that particular attention be paid to incentives, either productive or counterproductive, that could influence the performance of the WSS service. It also suggests identifying vested interests likely to be affected by reforms, with a focus on those engaged in fraud and corruption, as they could actively lobby against reforms which, if successfully implemented, would affect their revenues. The note focuses primarily on the provision of official piped WSS service, but it also recognizes that when a central service provides limited coverage or poor performance it can forfeit its monopoly status, whereupon alternatives to the piped WSS service often play an important role. The note also stresses the need for identifying weak links of the accountability framework as they could encourage fraud or corruption. The note finally summarizes best practice for setting WSS tariff levels and structures and for designing subsidies that reach those who need them.